Homeless and At-Risk Information (Distributed by ERIC Clearinghouse, 1991)
This document reports information and lists resources for educating homeless and at-risk populations in Iowa. Organized into 12 sections that are grouped into three areas, the document provides research reports, listings of resources, and policy guidelines. Sections I through III, titled "Homeless Information," contain the following: (1) "Homelessness in Iowa: the 1990 Report" (Drake University, Iowa), which reports a study on the educational needs of the Iowa's homeless students; (2) "Homeless Students: New Rules" (W. Lepley), which outlines state policies; and (3) "Educating Homeless Children and Youth: Problems and Solutions" (Iowa Department of Education). Sections IV through X, "At-Risk Planning Materials," include the following: (4) a description of school-based youth services programs; (5) "Guidelines for Serving At-Risk Students" (Iowa Department of Education); (6) "Inventory of Policies and Practices Related to Student Failure and Dropping Out" (Iowa Department of Education); (7) an outline of activities and services for students needing additional assistance; (8) "Students At-Risk: Planning Worksheet for Educators" (R. E. Morley); (9) "Services (Phase III) for At-Risk Student Populations: Preschool-12" (R. E. Morley and S. Surbaugh); and (10) "At-Risk Populations: Summary of Financial Resources for Program Development" (Iowa Department of Education). Sections XI and XII, "Alternative Programs," contain the following: (11) "Alternative Schools, Programs, and Support Services for Dropouts and Dropout Prevention in Iowa According to School District" (R. E. Morley); and (12) a list of media resources. (JB)